Functional electrical stimulation improves brain perfusion in cranial trauma patients - Bárbara Juarez Amorim; Allan de Oliveira Santos; Telma Dagmar Oberg; Juliana Romanato; Dalton A. Anjos; Mariana da Cunha Lopes de Lima; Celso Darío Ramos; Donizete Cesar Honorato; Edwaldo Eduardo Camargo; Elba Cristina de Sá Camargo Etchebehere (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Demonstrate brain perfusion changes due to neuronal activation after functional electrical stimulation (FES). METHOD: It was studied 14 patients with hemiplegia who were submitted to a program with FES during fourteen weeks. Brain perfusion SPECT was performed before and after FES therapy. These patients were further separated into 2 groups according to the hemiplegia cause: cranial trauma and major vascular insults. All SPECT images were analyzed using SPM. RESULTS: There was a significant statistical difference between the two groups related to patient's ages and extent of hypoperfusion in the SPECT. Patients with cranial trauma had a reduction in the hypoperfused area and patients with major vascular insult had an increase in the hypoperfused area after FES therapy. CONCLUSION: FES therapy can result in brain perfusion improvement in patients with brain lesions due to cranial trauma but probably not in patients with major vascular insults with large infarct area.